Gastroprotective effect of mucilage fraction from Solenostemma argel via cytoprotection and attenuation of oxidative stress, inflammation and apoptosis - Riham A. El-Shiekh; Abeer Salama; Asmaa K. Al-Mokaddem; Essam A. Abdel-Sattar (Shahrekord University of Medical Sciences, 2021)
Introduction: Polysaccharides have numerous therapeutic values including immunity stimulation, angiotensin converting enzyme inhibition, wound healing, anti-diabetic and cytotoxic activities, in addition to their potent anti-oxidant properties. This work examined the gastroprotective and ulcer healing potential of mucilage fraction isolated from Solenostemma argel (Delile) Hayne (MFA) against ethanol-induced gastric ulcer in rats. Methods: Forty Sprague-Dawley rats were divided into five groups (n=8); normal control (I), ethanol control (II), 20 mg/kg Antodine pretreated rats (III), 100 mg/kg, and 200 mg/kg MFA pretreated rats, respectively (IV & V). All rats in groups II-V received single intragastric dose of ethanol (5 mL/kg) to induce gastric ulcer. Gastric mucosal injuries were assessed by stomach gross examination as well as histopathology, and immunohistochemistry of apoptotic markers. Also, several biochemical parameters including oxidative stress, proinflammatory cytokines, cytoprotective and cell proliferative biomarkers were measured. Results: High-performance liquid chromatography (HPLC) analysis of MFA revealed its composition of glucose, D-fucose and N-acetyl glucosamine as monosaccharaides, in addition to glucuronic and galacturonic acids. The data showed that MFA, 200 mg/kg had potent antioxidant, anti-inflammatory, cytoprotective, cell proliferative, and antiapoptotic activities which were better than Antodine. Conclusion: This study revealed that MFA had significant gastroprotective effects against ethanol-induced gastric injuries and could be a promising adjuvant therapy for ulcer treatment.